The Impact Of Population and Taxes On Economic Growth In Maluku Province: An Empirical Analysis - Kipeleleway, Agustinus; Oppier, Hermi; Pattimahu, Terezia V.; Hahury, Hendri D. (Convergence: The Journal of Economic Development, 2024)
Abstract This study aims to examine the influence of population size and tax variables on economic growth in Maluku Province, Indonesia. The study employs a descriptive quantitative method utilizing secondary data obtained from the Central Bureau of Statistics of Maluku Province, consisting of time series data from 2002 to 2022. The data were analyzed using a multiple linear regression model with the assistance of EViews 9 software. The results of the study show that, partially, population has a positive effect on economic growth in Maluku Province, while taxes have a negative effect on economic growth in in Maluku Province. The model exhibits a high explanatory power, with an R² value of 95.6%, indicating that the interplay between population dynamics and fiscal policy substantially accounts for variations in economic performance. These results underscore the necessity for integrated policy approaches that leverage demographic potential while addressing fiscal inefficiencies. Accordingly, the study recommends strategic investments in human capital development, tax administration reform, and infrastructure tailored to the province's archipelagic geography. Such measures are imperative for fostering inclusive and sustainable regional growth in the context of Indonesia's diverse economic landscape. Keywords :  Economic growth, Population, Taxes Abstrak Penelitian ini bertujuan untuk mengetahui pengaruh variabel jumlah penduduk dan pajak terhadap pertumbuhan ekonomi di Provinsi Maluku, Indonesia. Penelitian menggunakan metode kuantitatif deskriptif dengan data sekunder dari Central Bureau of Statistics Provinsi Maluku berupa data time series tahun 2002 hingga 2022. Data kemudian dianalisis menggunakan model regresi linier berganda dengan bantuan software Eviews 9. Hasil penelitian menunjukkan bahwa secara parsial, jumlah penduduk memiliki pengaruh positif terhadap pertumbuhan ekonomi di Provinsi Maluku, sedangkan pajak memiliki pengaruh negatif terhadap pertumbuhan ekonomi di Provinsi Maluku. Model ini memiliki daya jelas yang tinggi, dengan nilai R² sebesar 95,6%, yang mengindikasikan bahwa interaksi antara dinamika kependudukan dan kebijakan fiskal secara substansial menjelaskan variasi kinerja ekonomi. Hasil ini menegaskan perlunya pendekatan kebijakan yang terintegrasi, yang memanfaatkan potensi demografis sembari mengatasi inefisiensi fiskal. Oleh karena itu, penelitian ini merekomendasikan investasi strategis dalam pengembangan sumber daya manusia, reformasi administrasi perpajakan, dan pembangunan infrastruktur yang disesuaikan dengan karakteristik geografis kepulauan. Langkah-langkah ini sangat penting untuk mendorong pertumbuhan regional yang inklusif dan berkelanjutan dalam konteks keragaman ekonomi Indonesia.  Kata kunci:  Pertumbuhan ekonomi, Penduduk, Pajak